PENGARUH PENILAIAN PRESTASI KERJA DAN LOYALITAS KARYAWAN BAGIAN PRODUKSI RIGID BOX TERHADAP PROMOSI JABATAN PADA PT. SATYAMITRA KEMAS LESTARI TBK. - Egit Prayitno; Christina Natalina; Frangky Yosua Sitorus (Buletin Ekonomi, 2023)
This research study is intended to provide information related to the impact of research on performance appraisal and employee loyalty in the Rigid Box Production Section on promotions at PT. Satyamitra Kemas Lestari. Descriptive quantitative methods and data collection techniques, namely questionnaires, are the methods in this research study. A computer application called SPSS with version 24 is a tool for analyzing the data found in this research study. The findings in this research study are the t test (partial) of the Job Performance Assessment variable (X1) for Promotion (Y) with the findings of t count & t table of 17,620 & 1,990, the conclusion is that Ha is rejected and Ho is accepted, the impact of variable X1 on variable Y of the findings of the multiple regression table, the beta column is 0.891 or 8.91%. t test findings (partial) for the variable Employee Loyalty (X2) on Promotion (Y) obtained t count & t table a total of 24,662 & 1,990 the conclusion is that Ha is rejected and Ho is accepted, the impact (X2) on (Y) findings from the multiple regression table, the beta column is 0.939 or 93.9%. Adjust R Square value = 0.879 with exposure to Performance Appraisal (X1) and Employee Loyalty (X2) on Promotion (Y) of 87.9%, the remaining 12.1% is affected by other factors not examined in this research study. Keywords: Job Performance, Employee Loyalty and Promotion